Teaching American Media and Popular Culture: Expansion, Inclusion, Interdisciplinarity - Joel Frykholm (American Studies in Scandinavia)
This is a reflection on my experiences in teaching American media at the Swedish Institute for American studies from 2015 to 2021. By way of concrete descriptions of classes taught and topics raised, I make a case for an approach to popular media that looks beyond both an all-too-limited focus on “mass media” and the text-centric, hermeneutically based discussions about media representations that have otherwise been the most common way of engaging with media in American studies. I also discuss challenges of interdisciplinarity that are a key concern not only when teaching media, but for the field of American studies more broadly.